BAR Interviews Yigael Yadin - Shanks, Hershel 1930-2021 (1983)
On July 22, 1982, BAR editor Hershel Shanks visited Yigael Yadin in his home in Jerusalem. Shanks spoke for several hours with Yadin, who had recently returned to full time archaeology after one of the many discursions that have marked his amazing life. Yadin has had a number of careers—soldier, scholar and politician among […]